(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Nephrotic syndrome (NS) is a frequent chronic illness marked by changes in permselectivity at the glomerular capillary wall, as a result, it is unable to limit protein loss through the urine. Bacterial and viral infections are more common in patients with NS. Human Bocavirus (HBoV) is an emerging pathogen suspected to cause respiratory and GIT infections in children. Objective: To investigate the frequency of HBoV in children with NS who have acute upper respiratory tract infections, and compare it with normal controls. Methods: A case-control study carried out on 120 nasal swabs from children divided into three groups; 40 children each group (nephrotic syndrome and immunocompetent children with acute upper respiratory tract infections, and apparently children in good health without respiratory infections as control group). Viral DNA extracted from these samples and HBoV detected using real-time polymerase chain reaction. Results: HBoV was detected in 30 (75%) of patients with NS, and 18 (45%) in normal children with acute upper respiratory infections, while it was 3 (7.5%) in apparently healthy control group. The mean cycle threshold (CT) of HBoV in the three groups were 18.99 in nephrotic patients, 20.21 in normal children with acute upper respiratory infections and 24.33 in control group Conclusion: HBoV is relatively common among nephrotic children with acute upper respiratory infection, with a lowest CT (high viral load) as compared to the apparently normal children with acute upper respiratory infections and children in good health. Keywords: Nephrotic syndrome, Human Bocavirus, acute upper respiratory infections, children Citation: Lazim HH, Ali SH, Salim AB. Detection of Human Bocavirus in nephrotic syndrome children with acute upper respiratory tract infections. Iraqi JMS. 2023; 21(1): 108-112. doi: 10.22578/IJMS.21.1.11